The Mediating Role of Brand Love in the Relationship between Brand Trust and Word-of-Mouth: A Field Study in the Egyptian Market - El-Sherif, Ahmed Mohamed Mahran (The Arab Journal of Administration, 2025)
The aim of this research is to examine the mediating role of brand love in the relationship between brand trust and word-of-mouth. The research population consisted of customers interacting with brands in the Egyptian market. The total number of analyzable questionnaires was 388, with data collected via both electronic and paper-based Questionnaires. Statistical tools such as descriptive analysis, confirmatory factor analysis, and structural equation modeling to analyze the data. The key contributions of this study include the following findings: a significant and strong positive effect of brand trust on word-of-mouth; a significant and strong positive effect of brand love on word-of-mouth; and a significant and strong positive effect of brand trust on brand love. Finally, the study confirmed the positive, significant, and overall mediating role that brand love plays in the relationship between brand trust and word-of-mouth, which is the unique contribution of this research. Based on these findings, the study provides several recommendations for brand managers and marketing professionals in companies operating within the Egyptian market. Based on these findings, several recommendations have been proposed for brand and marketing managers in companies operating in the Egyptian market. Among the most important are enhancing customer trust in the brand by reinforcing a sense of reliability, security, and integrity; improving passion, fascination, and the emotional aspects associated with it, which contribute to strengthening positive word-of-mouth. Additionally, a strategic linkage should be established between trust and customer brand love, alongside the activation and integration of complaint management with compensation management within companies to improve word-of-mouth.